FACIAL NERVE INJURY IN TEMPORAL BONE FRACTURES DUE TO ROAD TRAFFIC ACCIDENTS: RADIOLOGICAL PREDICTORS AND CLINICAL OUTCOMES (Asian Journal of Medical Research and Health Sciences, 2026)
Background:  Temporal bone fractures are a frequent consequence of high-velocity road traffic accidents and are often associated with facial nerve injury, a complication that significantly affects functional, psychological, and social outcomes. Early identification of radiological predictors of facial nerve involvement is crucial for timely intervention and prognostication. Despite advances in high-resolution computed tomography (HRCT), variability persists in predicting facial nerve injury and correlating imaging findings with clinical outcomes. Objectives:  To evaluate the incidence of facial nerve injury in patients with temporal bone fractures resulting from road traffic accidents, to identify radiological predictors associated with facial nerve involvement, and to assess clinical outcomes following conservative or surgical management in a tertiary care hospital setting. Materials and Methods: This prospective observational study will be conducted at a tertiary care hospital over a defined study period. Patients presenting with temporal bone fractures secondary to road traffic accidents will be enrolled based on predefined inclusion and exclusion criteria. All participants will undergo detailed clinical evaluation, including facial nerve assessment using the House–Brackmann grading system, and radiological evaluation using high-resolution computed tomography of the temporal bone. Radiological parameters such as fracture orientation, involvement of the facial nerve canal, otic capsule violation, and associated intracranial injuries will be analyzed. Clinical outcomes will be assessed during follow-up, focusing on facial nerve recovery, hearing status, and need for surgical intervention. Statistical analysis will be performed to determine significant associations between radiological predictors and clinical outcomes. Results: The study is expected to demonstrate a significant association between specific radiological features particularly facial nerve canal involvement, transverse or mixed fracture patterns, and otic capsule violation and the severity as well as prognosis of facial nerve injury. Early radiological predictors are anticipated to correlate strongly with poorer facial nerve outcomes and increased need for surgical management. Conclusion: Radiological evaluation using HRCT plays a pivotal role in predicting facial nerve injury and guiding management strategies in temporal bone fractures due to road traffic accidents. Identification of reliable imaging predictors enables early risk stratification, optimized treatment planning, and improved functional outcomes. This study emphasizes the importance of an integrated radiological–clinical approach in the management of temporal bone trauma at tertiary care cente.